UPAYA PENINGKATAN LITERASI MELALUI POJOK BACA DENGAN PEMANFAATAN BAHAN BACAAN YANG BERMUTU DI DESA MEREMBU - Listyputri, Alyssa Zahra; Jurnal Wicara; Wibowo, Wahyu; Permatasari, Tri; Afriani, Sukma; Samami, Shahib; Nurkhalizah; Rasuma, Nonik; Asbi, M.; Maulida, Khairani; Amita; Nurmawanti, Iva (Jurnal Wicara, 2025)
Literacy programs play an important role in improving the quality of human resources from an early age, especially in areas with limited access to reading materials such as Merembu Village, West Lombok. This study aims to examine the effectiveness of the Mataram University Community Service Program (KKN) in improving children's literacy through a participatory approach. The method used is Participatory Action Research (PAR) involving children, teachers, parents, and village officials. The main activities included managing reading corners, optimizing the Community Reading Park, reading aloud, reviewing books intelligently, reading-based projects, writing simple stories, and village-level literacy appreciation. The results of the study showed an increase in children's interest in reading, text comprehension, critical thinking, creativity, and courage in expressing ideas. Constraints in the form of limited literacy facilities can be overcome through adaptive strategies by KKN students who provide alternative reading access. Thus, the literacy KKN program is effective in fostering a reading culture and has the potential to be sustainable through the strengthening of facilities and community collaboration.